Effect of Ti addition on mixed microstructure of allotriomorphic and bainitic ferrite in wrought C-Mn steels - Cho, YW; Byun, JS; Shim, JH (TRANS TECH PUBLICATIONS LTD, 2003)
The influence of Ti addition on the microstructure of hot-deformed C-Mn steel has been investigated. The C-Mn steels of 0.1 and 0.15 wt% C have been deformed at different temperatures and cooled at various rates. The small addition of Ti induces a reduction in the prior austenite grain size (PAGS) and an increase in the non-recrystallization temperature of deformed austenite grains. The addition of Ti also modifies the bainitic ferrite microstructure by intragranular nucleation on Ti2O3 inclusions. For relatively coarse austenite grains of about 60 mum, the microstructure mainly consisting of acicular ferrite is developed at appropriate cooling rates according to the hardenability. A mixture of very small packets of bainite and acicular ferrite is obtained for fine austenite grains of about 30 mum. For unrecrystallized austenite grains, the cooling rates similar to those of the recrystallized austenite grains of 60mum are appropriate to get the positive effects of the Ti addition.
Keywords: ACICULAR FERRITE; NUCLEATION